Acoustic emission method for investigation of functional materials - Lyashenko, O.V.; Kravtsov, M.V.; Veleschuk, V.P. (Functional Materials, 2004)
The analysis of the experimental results is carried out at examination of acoustic emission (AE) at dynamic and statical actions. It is shown, that threshold origin AE is accompanied time or stationary values by modifications in dependences of performances and properties of the functional materials (FM) on quantity of the given action. These modifications can be explained by acceleration of processes of relaxation and the degradation, accompanying origin AE at reorganization of structure in local fields FM. Проведен анализ экспериментальных результатов при исследовании акустической эмиссии (АЭ) при динамическом и статическом воздействиях. Показано, что пороговое возникновение АЭ сопровождается временными или постоянными изменениями в зависимостях характеристик и свойств функциональных материалов (ФМ) от величины данного воздействия. Эти изменения могут быть объяснены ускорением процессов релаксации и деградации, сопровождающих возникновение АЭ при перестройке структуры в локальных областях ФМ. Проведено аналіз експериментальних результатів при дослідженні акустичної емісії (АЕ) при динамічному та статичному впливі. Показано, що порогове виникнення АЕ супроводжується тимчасовими або постійними змінами в залежностях характеристик та властивостей функціональних матеріалів (ФМ) від величини даного впливу. Ці зміни можуть бути пояснені прискоренням процесів релаксації та деградації, що супроводжують виникнення АЕ при перебудові структури у локальних областях ФМ.